2016
DOI: 10.7324/japs.2016.60932
|View full text |Cite
|
Sign up to set email alerts
|

Effects of menthone and piperitone on growth, chlorophyll a and beta-carotene production in Dunaliella salina

Abstract: Recently, studying essential oils and secondary metabolites of plants and microalgae have received much attention. The biosynthesis of the secondary metabolites is strongly influenced by different environmental factors. Monoterpenes as a main fraction of essential oils of fruits and vegetables have many clinical applications. They could inhibit the carcinogenesis processes and therefore might be effective in treatment of cancers. Dunaliella salina, a photosynthetic green microalga is known as a rich source for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Zarei and collab. investigated the effects of some monoterpenes (menthone and piperitone) isolated from Dunaliella salina on a concentration of β-carotene and Chl a in some cultures [ZAREI et al 2016;PUTNOKY et al, 2013, BUTNARIU et al, 2014BUTNARIU and GIUCHICI, 2011] .…”
Section: Resultsmentioning
confidence: 99%
“…Zarei and collab. investigated the effects of some monoterpenes (menthone and piperitone) isolated from Dunaliella salina on a concentration of β-carotene and Chl a in some cultures [ZAREI et al 2016;PUTNOKY et al, 2013, BUTNARIU et al, 2014BUTNARIU and GIUCHICI, 2011] .…”
Section: Resultsmentioning
confidence: 99%
“…investigated the effects of some monoterpenes (мenthone and piperitone) isolated from Dunaliella salina on a concentration of β-carotene and chlorophyll "a" in some cultures. Authors found a decrease in their concentration in leaves treated with the мenthone and piperitone [ZAREI et al, 2016, BUTNARIU and CORADINI, 2012, PETRACHE, et al, 2014 . El-Said Salem reported that synthetic insecticides may have some side effects on the treatment of agricultural crops, such as a significant reduction in chlorophyll (a) and (b) content in maize and tomato leaves after application of malathion, chlorosane, etc.…”
Section: 343mentioning
confidence: 96%
“…The medium was maintained at room temperature (25°C). The cell concentration measurements were performed through an optical microscope (TNB-01B-Opton, Brazil) and hemocytometer (Zarei et al 2016).…”
Section: Microalgae and Culture Mediummentioning
confidence: 99%